Enhancing Batik Business Income through Digital Marketing and Entrepreneurship Orientation in Banyuwangi Regency - Dwiyanti, Yeni Hilma; Amalia, Dian Rizqi Nur; Handayani, Estu (Wiga : Jurnal Penelitian Ilmu Ekonomi, 2022)
This article aims to analyze the increase in income through digital marketing and entrepreneurial orientation consisting of innovation, proactiveness, and risk-taking for batik business actors in Banyuwangi Regency. Sampling was done using the purposive sampling method and obtained as many as 30 respondents as samples. Multiple linear regression analysis was used as the analytical method in this article. The results are that the digital marketing, innovation, proactive, and risk-taking variables positively affect the income variable. Digital marketing, innovation, proactive, and risk-taking variables can affect income variables. This shows that the increase in the income of batik business actors in Banyuwangi Regency can be influenced by digital marketing and entrepreneurial orientation, which consists of innovation, proactiveness, and risk-taking.